A Descriptive study to assess the Factors interfering with Glycemic Control among Type 2 Diabetes Mellitus patients - L. Ranganayk, Ankita; Kiranpreet, Kaur (International Journal of Nursing Research, 2023)
Aim: This study is conducted to assess factors interfering with good and poor glycemic control. Introduction: There is a rising trend in the prevalence of diabetes in India over recent years, poor and inadequate glycemic control affected by many factors such as socio-demographic, clinical and behavior factors constitutes a major risk factor for the development of diabetes complications. Materials and Methods: A descriptive study was conducted using purposive sampling technique by enrolling 100 subjects with type 2 Diabetes Mellitus having 30 and above 30 years of age, attending OPD or admitted in SGRD hospital. Data collected by observation and interviewing the subjects using self-structured questionnaire. Analysis and interpretation were done by descriptive and inferential statistics. Results: It shows that total of 100 subjects 61% had poor and 39% had good glycemic control. Factors such as age 50–59 years 18 (29.5%), male 36 (59%), informal education 30 (49.1%), BMI overweight 27 (44.3%), duration of diabetes 4–6 years, 30 (49.2%), and co-morbidities such as hypertension 38 (62.3%) and renal diseases 20 (32.8%), inappropriate diabetic diet 37 (60.7%), and 35 (57.4%) inadequate exercise alcohol consumption 26 (42.6%) were factors interfering glycemic control. Complications related to diabetes were 10 (16.4%) retinopathy and nephropathy, 23 (37.7%) neuropathy, 4 (6.6%) coronary artery disease, 8 (13.1%) foot ulcer, 15 (24.6%) stroke, 5 (8.2%) cataract and their odd ratios (OR-3.627, 7.45, 48.22, 6.18, 12.55, 18.09, 3.913, and 1.07, respectively). Conclusion: There is need to achieve an understanding of the extent of glycemic control in patients with type 2 DM and to see the factors interfering with good and poor glycemic control groups, and as a result, to spot the factors affecting glycemic control.